(untitled) (International journal of artificial intelligence, 2026)
In the context of rapid global changes and increasing social complexity, education systems are increasingly expected to support not only cognitive development but also the formation of socio-emotional competencies necessary for successful life and professional activity. One of the most significant competencies of the 21st century is responsible decision-making. Social and Emotional Learning (SEL) has emerged as an effective pedagogical approach aimed at developing emotional intelligence, social awareness, and responsible behavior among students. This article examines the pedagogical potential of SEL as a mechanism for developing responsible decision-making competencies in adolescents. The study analyzes the theoretical foundations of SEL, its structural components, and its impact on adolescents’ ability to make balanced and ethical decisions. The article highlights the role of educational environments, teacher facilitation, and integrated pedagogical strategies in fostering decision-making competence. The findings suggest that SEL-based educational practices contribute significantly to adolescents’ emotional self-regulation, critical reflection, and socially responsible behavior. The integration of SEL into school curricula can therefore serve as an effective strategy for promoting holistic student development and preparing young people for the challenges of modern society.